A World-Class Education-Based Pesantren Ecosystem Model: Integrating Digitalisation, Financing and Welfare, and Character Education at Al-Ashriyyah Nurul Iman Islamic Boarding School, Parung, Bogor - Argunaini, Sri; Syahran, M.; Latif, Mukhtar; Fuad, Kemas Muhammad; Fauzan, Fauzan (Lembaga Teewan Journal Solutions, 2026)
This article develops a World-Class Education (WCE)-based pesantren ecosystem model integrating three subsystems commonly examined separately: educational digitalization, financing and welfare, and character education. Employing a qualitative documentary case-study design at Al-Ashriyyah Nurul Iman Islamic Boarding School in Parung, Bogor, data were drawn from three previous papers, regulations, official institutional publications, international organisation reports, and academic literature, analysed through data condensation, thematic coding, cross-source comparison, and conceptual proposition building. The evidence points to relatively developed digitalization at Nurul Iman in administration, TABANI transactions, media, and entrepreneurial skills, whereas pedagogical integration, teachers' digital competence, data governance, and AI policies remain poorly documented; its financing system draws on well-established low-cost education, waqf, philanthropy, and business units, though per-student costing, remuneration, reserves, and risk management are only thinly evidenced; and character education rests on a 24-hour architecture, role modelling, moral authority, habituation, and peer control, tempered by observable risks of figure dependency and externally driven compliance. On this basis, the article puts forward, as a conceptual proposition awaiting further validation, a Pesantren WCE Ecosystem Model linking the three subsystems through leadership, data, quality assurance, human protection, and continuous evaluation, and recommends strengthening financial governance while formalizing digital and AI policies to help realize the model.